2000
DOI: 10.1161/01.cir.101.8.841
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Shed Membrane Microparticles With Procoagulant Potential in the Peripheral Circulating Blood of Patients With Acute Coronary Syndromes

Abstract: Background-Apoptotic microparticles are responsible for almost all tissue factor activity of the plaque lipid core. We hypothesized that elevated levels of procoagulant microparticles could also circulate in the peripheral blood of patients with recent clinical signs of plaque disruption and thrombosis. Methods and Results-We studied 39 patients with coronary heart disease, including 12 patients with stable angina and 27 patients with acute coronary syndromes (ACS), and 12 patients with noncoronary heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
618
7
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(658 citation statements)
references
References 22 publications
21
618
7
10
Order By: Relevance
“…It is known, however, that microparticles rich in phosphatidylserine can participate in the dissemination of proadhesive and procoagulant activities in thrombotic disorders (11,16,17,26,34), a property which could potentially contribute to the vascular pathology seen in vasculitic syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known, however, that microparticles rich in phosphatidylserine can participate in the dissemination of proadhesive and procoagulant activities in thrombotic disorders (11,16,17,26,34), a property which could potentially contribute to the vascular pathology seen in vasculitic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, plasma from patients with APS, MS, or TTP was shown to induce the formation of EMPs from endothelial cells in tissue culture (11,18,19). EMPs exhibit prothrombotic potential, which is mediated by activation of the extrinsic coagulation pathway (i.e., the tissue factor/factor VII-dependent pathway) (11,16,17,(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…Besides different advantages in technical ease, invasiveness, and reliability, a major difference is whether macro-or microvascular beds are intended to be examined. Biomarkers such as ET-1, circulating endothelial microparticles, and progenitor cells can be analyzed [28].…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…Enhanced lipid peroxidation leading to formation of oxidized phospholipids was observed in acute lung injury syndromes such as ARDS, ventilator-induced lung injury, and asthma (Chabot, Mitchell et al 1998;Wood, Gibson et al 2003). An increased release of membrane vesicles containing oxidized phospholipids has been detected as a result of tissue injury and apoptosis (Holme, Solum et al 1994;Huber, Vales et al 2002), and such membrane vesicles were also observed in patients with acute lung injury, cardiac ischemia, acute coronary syndrome and in pathological settings with platelet activation (Holme, Solum et al 1994;Mallat, Benamer et al 2000).…”
Section: Introductionmentioning
confidence: 99%